Predicting performance of a ground-source heat pump system using fuzzy weighted pre-processing-based ANFIS - Esen, Hikmet; Inalli, Mustafa; Sengur, Abdulkadir; Esen, Mehmet (Pergamon-Elsevier Science Ltd, 2008)
The goal of this work is to predict the daily performance (COP) of a ground-source heat pump (GSHP) system with the minimum data set based on an adaptive neuro-fuzzy inference system (ANFIS) with a fuzzy weighted pre-processing (FWP) method. To evaluate the effectiveness of our proposal (FWP-ANFIS), a computer simulation is developed on MATLAB environment. The comparison of the proposed hybridized system's results with the standard ANFIS results is carried out and the results are given in the tables. The efficiency of the proposed method was demonstrated by using the 3-fold cross-validation test. The statistical methods, such as the root-mean squared (RMS), the coefficient of multiple determinations (R-2) and the coefficient of variation (cov), are given to compare the predicted and actual values for model validation. The average R-2 values is 0.9998, the average RMS value is 0.0272 and the average cov value is 0.7733. which can be considered as very promising. The data set for the COP of GSHP system available included 38 data patterns. The simulation results show that the FWP-based ANFIS can be used in an alternative way in these systems. The prediction results of the proposed structure were much better than the standard ANFIS results. Therefore, instead of limited experimental data found in the literature, faster and simpler solutions are obtained using hybridized structures such as FWP-based ANFIS. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Ground-source heat pump; Adaptive neuro-fuzzy inference system; Membership functions; Fuzzy weighted pre-processing; Coefficient of performance